A Case of Transient, Isolated Cranial Nerve VI Palsy due to Skull Base Osteomyelitis. (15th June 2014) - Patel, Brijesh; Souqiyyeh, Anas; Ali, Ammar
Abstract : Otitis externa affects both children and adults. It is often treated with topical antibiotics, with good clinical outcomes. When a patient fails to respond to the treatment, otitis externa can progress to malignant otitis externa. The common symptoms of skull bone osteomyelitis include ear ache, facial pain, and cranial nerve palsies. However, an isolated cranial nerve is rare. Herein, we report a case of 54-year-old female who presented with left cranial nerve VI palsy due to skull base osteomyelitis which responded to antibiotic therapy.